Improved LEACH protocol algorithm for WSN based on energy balance and high efficiency - Li-xiao HUANG; Hui WANG; Li-yong YUAN; Ling-guo ZENG (Tongxin xuebao)
The improved energy-saving algorithm for the energy efficient and balanced protocol (LEACH-improved) was proposed.In the algorithm,the residual energy factor,the distance factor and the node density factor was added to improve the threshold formula.Moreover,in the various application scenarios of WSN,based on the different effects on the selection of cluster heads caused by the residual energy and geographical location,the weighting factor was introduced.Results of simulation experiments show that the improved algorithm can effectively reduce the network energy consumption and prolong the network lifetime.